Mindbend: Robin Cook. New York: Signet, 1985. 346pp - Amatya, Shripa (Journal of Kathmandu Medical College, 2017)
Not available.Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, Page: 136-136